Single Axis Quadcopter menggunakan Proporsional Integral Derivative (PID) berbasis Labview - Rivaldi Priansyah (Telekontran : Jurnal Ilmiah Telekomunikasi, Kendali dan Elektronika Terapan, 2016)
Abstract - Quadcopter is a Miniature Aerial Vehicle (MAV) that has 4 propellers with the ability to take off, land vertically and the ability to negotiate a narrow space that allows it to be used in a messy indoor area. Because of this ability the quadcopter has recently been considered for various applications both in the military and civilian fields. In particular, quadcopter has been explored for applications such as surveillance and disaster exploration. Quadcopter is currently widely used because it has the ability to make movements that are difficult for other types of aircraft, as well as the ability to fly and land vertically in a narrow place with a complete system of rotor stability mechanisms. In this study an automatic simulation was carried out on a laptop with Labview-based programming software, the simulation in this study only used one angle on the quadcopter so that it only needed 2 motors as propeller drives or commonly called single axis quadcopter. An integral derivative (PID) controller for roll angle movement on a single shaft quadcopter is expected to be able to restore the roll position according to the setpoint and support to optimize. A control system is needed to adjust roll angle movement, so that it can move stably and be able to overcome a given disturbance. As a roll angle movement controller PID controller is used, whose parameters are determined by the Labview application program. This PID parameter in the program in Labview as well as experiment simulation. Based on the calculation results, get the value Kp = 0.8, Ki = 25, Kd = 0.004. The control system is able to reduce oscillation with a 2 degree error rate from the input. With the PID coefficient the system is able to restore the roll angle condition when given a simulation error. Keyword : Single Axis Quadcopter, Quadcopter, PID, roll, Labview